International economics - Dunn, Robert M.; Mutti, John H. (London ; New York : Routledge, 2004)
The latest edition of International Economics improves and builds upon the popular features of previous editions. The graphs, tables and statistics are all updated and improved sections have also been added on the following topics: New developments in international trade agreements and the latest round of international trade talks, International financial crises. A new section on current controversies in the international monetary system. With impressive pedagogy, learning objectives and summaries, this clearly written book will be another winner with students of international economics and business.
Includes bibliographical references and index.
rpm 06/06/14
Loans
Keywords: International economic relations